C2O4(SnPh3)2 ISOMERS AND SOME OF THEIR ADDUCTS: SYNTHESIS AND SPECTROSCOPIC CHARACTERIZATION - YAYA SOW; CHEIKH ABDOUL KHADIR DIOP; LIBASSE DIOP; BERNARD MAHIEU; LORENZO STIEVANO (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The study of the interactions between C2O4(SnPh3)2 and a Lewis base (Ph3PO) or salts such as Ph4PCl, (Bu2NH2)2C2O4.3H2O, (Pr2NH2)2C2O4(Cy2NH2)2C2O4.2H2O have yielded seven new adducts, infrared and Mossbauer studies which have been carried out. The suggested structures are discrete or of infinite chain type. Most of the structures contain C2O4(SnPh3)2 with cis coordinated SnPh3 residues characterized for the first time in this work. In Ph3PO containing adducts the Lewis base coordinates a SnPh3 residue. The oxalate behaves as a mo- or bidentate, a mono- or bichelating, a only hydrogen bonds involved ligand. In the structures of the compounds containing a non symmetrical cation, this one is involved in N-H…O hydrogen bonds.